“Kelulut” stingless bee culture of Datai Lino farmer group in Bentian Besar Village, Kutai Barat, Indonesia - Syafrizal Fachmy; Rudy Agung Nugroho; Rudianto Rudianto; Widha Prahastika (Fakultas MIPA Universitas Negeri Padang, 2019)
A Community service program known as Program Kemitraan Masyarakat (PKM) was done from April-July 2019 at Bentian Besar village, Bentian Kutai Barat, Kalimantan Timur. The purpose of the PKM was to empower community, especially Datai lino farmer group in order to enhance their productivity and transfer Science and technology, assisting the member of Datai lino farmer group to do stingless bee culture. In this program, the member of farmer group has obtained a soft skill and an experience in stingless bee culture. Further, this program can empower the member of Datai lino farmer to be an entrepreneurship, providing stingless bee product such as propolis and honey bee which has an economic value. This program was done in two sections, theory and practice with ratio 25%:75%. In theory section, the member of PKM has delivered a presentation regarding stingless bee culture technique. In the practice section, the members of datai lino farmer group directly built stingless bee home base and applied stingless bee culture, including maintenance bee colony and harvest the products. The outcome of the PKM program was soft skill transfer technology, a stingless bee culture module. In the future, this program can be implemented to boost the economic value for the members of Datai lino farmer group in Bentian, Kutai Barat, Kalimantan Timur.